Reducing the health disparities of Indigenous Australians: time to change focus - Durey, Angela; Thompson, Sandra (BioMed Central, 2012)
Background: Indigenous peoples have worse health than non-Indigenous, are over-represented amongst the poor and disadvantaged, have lower life expectancies, and success in improving disparities is limited. To address this, research usually focuses on disadvantaged and marginalised groups, offering only partial understanding of influences underpinning slow progress. Critical analysis is also required of those with the power to perpetuate or improve health inequities. In this paper, using Australia as a case example, we explore the effects of ‘White’, Anglo-Australian cultural dominance in health service delivery to Indigenous Australians. We address the issue using race as an organising principle, underpinned by relations of power.Methods: Interviews with non-Indigenous medical practitioners in Western Australia with extensive experience in Indigenous health encouraged reflection and articulation of their insights into factors promoting or impeding quality health care to Indigenous Australians. Interviews were audio-taped and transcribed. An inductive, exploratory analysis identified key themes that were reviewed and interrogated in light of existing literature on health care to Indigenous people, race and disadvantage. The researchers’ past experience, knowledge and understanding of health care and Indigenous health assisted with data interpretation. Informal discussions were also held with colleagues working professionally in Indigenous policy, practice and community settings.Results: Racism emerged as a key issue, leading us to more deeply interrogate the role ‘Whiteness’ plays in Indigenous health care. While Whiteness can refer to skin colour, it also represents a racialized social structure where Indigenous knowledge, beliefs and values are subjugated to the dominant western biomedical model in policy and practice. Racism towards Indigenous patients in health services was institutional and interpersonal. Internalised racism was manifest when Indigenous patients incorporated racist attitudes and beliefs into their lived experience, lowering expectations and their sense of self-worth.Conclusions: Current health policies and practices favour standardised care where the voice of those who are marginalised is often absent. Examining the effectiveness of such models in reducing health disparities requires health providers to critically reflect on whether policies and practices promote or compromise Indigenous health and wellbeing - an important step in changing the discourse that places Indigenous people at the centre of the problem.